Supplice - Cotler, T. Zachary, 1981- (Book collections on Project MUSE., 2014)
Winner of the 2014 Colorado Prize for Poetry. Supplice is the second installment in T. Zachary Cotler's sonnet sequence that began with Sonnets to the Humans. "Supplice," the systematic infliction of physical and/or mental torture, is both the subject and the main character of this sequence. These are amatory sonnets, but with love and rhyme tortured into broken and boneset textures. Supplice herself, the dark lady of these sonnets, is difficult to pin down with an epithet. Is she the angel of reality, banality, popular culture, pornography, uncertainty, or economic and environmental crisis?